(untitled) (Fiep Bulletin - online, 2013)
The rehabilitation center of the Faculdade Assis Gurgacz (FAG) since 2006 serves as a service of high complexity in rehabilitation, through the Unified Health System (SUS), in the city of Cascavel, Parana, given the population with multidisciplinary rehabilitation and making dispensing prostheses.This search have as objective to identify the users’ perception of the SUS, on the prosthesis received by the centre for rehabilitation of FAG, to verify as is dispensing prostheses and rehabilitation of users. The survey involved a sample of 51 amputees of the lower limbs prothetizade who responded to a questionnaire. The survey was conducted among dias18/04/2008 to 30/06/2008, all respondents were chosen randomly and signed the free end of informed consent. According to the results it was verified that 75% of users have made the process of adapting the prosthesis, and 67% are adapted to it. The sample was also found that 78% of users use the prosthesis daily and 82% have their AVD `s with a prosthesis. The views of users in the centre of rehabilitation of FAG showed that 6% consider the regular, 61% good and 33% expressed the view that the rehabilitation center is great. With the results of this study you can see that most users have a good perception of the prosthesis and rehabilitation offered.